Pengukuran Kualitas Hidup Pasien Hipertensi di Puskesmas Perumnas I Kota Pontianak yang Menggunakan Antihipertensi melalui EQ5D Questionnaire dan VAS - M Akib Yuswar; Nara Umillia Purwanti; Winda Zuraida (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
Hypertension can result a decrease in the quality of life of patients, so that an optimal type of antihypertensive therapy is needed. This study aimed to determine the differences in the quality of life of hypertension patients who use monotherapy drugs and a combination of hypertension in the Perumnas I Pontianak. The study design was observational cross-sectional with a purposive sampling technique, using convertion index of the European Quality of Life 5 Dimensions (EQ5D) Questionnaire and median values of Visual Analog Scale (VAS). As many as 25 out of 102 patients (24.5%) did not have problem in all five dimensions both monotherapy and a combination with the highest index of EQ5D 1,000. The problematic dimensions were in the dimensions of pain / discomfort (45.1%), walking/moving (35.3%), anxiety/depression (29.4%), usual activities (13.7%), and personal care (2.9%). The quality of life which was measured by VAS has a median value of 70 and there was no difference in quality of life between patients receiving antihypertensive monotherapy and combination.